Regulatory Role of N6-Methyladenosine (m6A) Modification in Osteoarthritis - Zhai, Ganggang; Xiao, Likang; Jiang, Chenyang; Yue, Songkai; Zhang, Meng; zheng, Jia; Liu, Zeming; Dong, Yonghui (Frontiers in Cell and Developmental Biology, 2022)
Osteoarthritis (OA) is one of the most common clinical joint diseases, and there are many opinions about its etiology and causative factors, but the molecular mechanisms underlying its development have not been fully elucidated. Current non-surgical treatment options for OA can not inhibit the progression of the disease significantly. Therefore, an in-depth understanding of the underlying molecular mechanisms of OA occurrence may help develop new therapeutic modalities. N-6-methyladenosine (m6A) is one of the most widely modified forms of RNA. In recent years, many studies have demonstrated that m6A modifications play an important role in the pathogenesis of OA. This paper reviews articles related to the role of m6A modifications in OA, highlighting the important role played by m6A modifications in RNA synthesis, transport and translation, and demonstrating the specific regulatory mechanisms of m6A-related proteins in the pathogenesis of OA, providing new ideas for the development of new therapeutic measures for OA.